Understanding the determinants of evaluation, adoption and routinisation of ERP technology (Enterprise Resource Planning) in the context of agricultural farms - Haberli Junior, Caetano (2019)
A thesis submitted in partial fulfillment of the requirements for the degree of Doctor in Information Management, specialization in Information and Decision Systems